Pengajaran dan Pengaplikasian Bahasa Inggris Formal dan Informal Bagi Siswa SMP di Jalan Akasia - Agus Darma Yoga Pratama (Warmadewa Press, 2020)
Teaching formal language is very important for children. In general, each person has the ability to acquire the first language, that is mother tongue based on the environt. It greatly influences person to tend to use informal language. The language learning can be divided into two, namely the in the classroom and outside of it. A teacher has a big responsibility for language development, especially for the development of students' language knowledge, especially English. The formulation of the problem in this study is how to improve students' understanding of the use of formal and informal English and to know the function of the two types of language. Therefore, a teacher should be able to provide a good understanding of the use of formal and informal language in accordance with certain situations. Based on the survey results, it was known that there were still many mistakes in the use of formal and informal English that were incompatible with the function and situation of using the two types of language both in spoken and written language. This research was designed using qualitative research with descriptive methods. This research was conducted with the aim of knowing the students' ability to use formal and informal English. The results shows that there is an increase in understanding the use of both formal and informal types of English.